Sistem Pendukung Keputusan Pemilihan Siswa/I Teladan Dengan Menggunakan Metode Multi-Objective Optimization on The Basis of Ratio Analisis (MOORA) - Ardi Kusuma; Amatilah Nasution; Reka Safarti; Rivalri Kristianto Hondro; Efori Buulolo (JURIKOM (Jurnal Riset Komputer), 2018)
The need for schools for applications for selecting student exemplars is something to consider. To meet these needs, a research will be conducted that will build an application and can provide an output recommendation for student election/example. The selection requires several criteria such as Report score, Attendance, Task value, and Achievement. The method used in building the decision support system of student selection is the Multi-Objective Optimization Method On The Basic Of Ratio Analyzer (MOORA). The final result obtained from this research is the application that can help the process of selecting the student / model because this application gives the output of student ranking recommendation from the biggest alternative value to the smallest through MOORA method. The application of decision support system of student elective/exemplar has been in accordance with the specification of functional requirement expected